ANALISA AUDIO STEREO DECODER UNTUK RADIO PENERIMA FM BERBASIS IC AN7410N - Ashari, M. Ibrahim; Faisol, Ahmad (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2017)
A stereo decoder is enabled to separate information and modulated signal by recovering the previous information signal come as one with the carrier signal using a varying frequency according to the amplitude change value that becomes the same information signal as the original signal or as stereo audio. Inside a stereo audio, there is a component which each functions to get the required signal results in the stereo decoder. The designed stereo decoder uses a single IC; IC AN7410N as a demodulator that is designed to demodulate the signal from the stereo encoder to the L and R audio signals. The result of the test shows that stereo decoder can detect the 19 kHz pilot tone frequency and stereo decoder can also receive FM radio broadcast from the sender and output audio results in the form of stereo L and R, even though the sideband frequency output measurement from each channel L and R, shows the frequency difference (Hz) of expected output frequency.Keywords: audio, stereo, decoder, AN7410N